Deuterium retention in the divertor tiles of JET ITER-Like wall. (August 2017) - Lahtinen, A.; Likonen, J.; Koivuranta, S.; Hakola, A.; Heinola, K.; Ayres, C.F.; Baron-Wiechec, A.; Coad, J.P.; Widdowson, A.; Räisänen, J.; ,
Highlights: D concentrations were determined for the JET ILW-2 divertor tiles with SIMS. The highest concentrations (∼8 · 10 18  D/cm 2 ) were found on the upper inner divertor. D retention is generally higher for ILW-2 divertor tiles than after ILW-1 campaign. Difference is related to longer exposure of some tiles and changes in SP-distribution. Abstract: Divertor tiles removed after the second JET ITER-Like Wall campaign 2013–2014 (ILW-2) were studied using Secondary Ion Mass Spectrometry (SIMS). Measurements show that the thickest beryllium (Be) dominated deposition layers are located at the upper part of the inner divertor and are up to ∼40 µm thick at the lower part of Tile 0 exposed in 2011–2014. The highest deuterium (D) amounts (>8 · 10 18  at./cm 2 ), in contrast, were found on the upper part of Tile 1 (2013–2014), where the Be deposits are ∼10 µm thick. D was mainly retained in the near-surface layer of the Be deposits but also deeper in tungsten (W) and molybdenum (Mo) layers of the marker coated tiles, especially at W–Mo layer interfaces. D retention for the ILW-2 divertor tiles is higher than for the first campaign 2011–2012 (ILW-1) and probable reasons for the difference are that SIMS measurements for the ILW-2 samples were done deeper than for the ILW-1 samples, some of the tiles were exposed during both ILW-1 and ILW-2 and therefore had a longer exposure time, and the differences between ILW-1 and ILW-2 campaigns e.g. in strike point distributions and injected powers.